Donor-Derived Disseminated Toxoplasmosis in a Liver Transplant Recipient With Documented Sulfa Allergy - Zoe Raglow; Emily Herriman; Gabriel Abrams; Marc Najjar; Christopher J. Sonnenday; Kevin S. Gregg (Case Reports in Transplantation)
Transplant recipients who are seronegative for Toxoplasma and receive an organ from a seropositive donor are at high risk for donor-derived toxoplasmosis in the absence of prophylaxis. While the risk in cardiac transplant recipients is well known, this infection is often underrecognized in noncardiac transplant recipients. Toxoplasmosis in transplant patients is associated with high mortality, and diagnosis is challenging as the presentation is nonspecific. Recommendations for prophylaxis in cardiac transplant recipients are well-defined, but the optimal prophylactic strategy in noncardiac transplant recipients, especially those with sulfa allergies, is unknown. We report a case of donor-derived disseminated toxoplasmosis in a liver transplant recipient who did not receive prophylaxis due to documented sulfa allergy. The patient subsequently underwent a challenge with trimethoprim/sulfamethoxazole and was successfully treated with this therapy. This case underscores the variable clinical presentation of donor-derived toxoplasmosis as well as the critical importance of accurate allergy evaluation pretransplant.